Risk Factors for Serious Suicide Attempts: Difference Between Older and Younger Attempters in the Emergency Department - Kim, Dong Wook; Cho, Seo Eun; Kang, Jae Myeong; Woo, Soo Kyun; Kang, Seung-Gul; Yeon, Byeong Kil; Cho, Seong-Jin (Frontiers in Psychiatry, 2021)
Objective: Suicide attempts of the older adults are known to be more serious than that of the younger adults. Despite its major social impact in South Korea, the behavioral mechanism of serious suicide attempt (SSA) in old people remains to be elucidated. Thus, we investigate the risk factors for SSA in older and younger adult groups. Methods: Demographic data, clinical information, and the level of seriousness of suicide with Risk Rescue Rating Scale were compared between older (age ≥ 65) and younger (age < 65) suicide attempters. Regression analyses were performed to identify the risk factors for SSA in these two groups. Results: Among 370 patients, 37 were older adults (10%; aged 74.41 ± 6.78), more likely to have another medical disease (p < 0.001), and a higher suicide completion rate (16.2% vs. 5.4%, p = 0.023). In the younger group, old age (B = 0.090, p < 0.001), male sex (B = -0.038, p = 0.019), and impression of schizophrenia (B = 0.074, p = 0.027) were associated with a higher risk-rescue ratio and interpersonal stress condition was associated with a lower risk-rescue ratio (B = -0.045, p = 0.006). In the older group, however, no variables were included significant in the regression model for the Risk Rescue Rating Scale. Conclusions: Demographic and clinical factors such as old age, male sex, interpersonal stress, and impression of schizophrenia were associated with high lethality in the younger suicide attempters. However, no factors were associated with SSA in the older adult group. Different mechanisms may underly the lethality in old age suicide.